Perjuangan Tokoh Perempuan dalam Novel Satin Merah Karya Brahmanto Anindito dan Rie Yanti - Utari Isnaini; Rina Ratih; Purwati Zisca Diana (STKIP PGRI Banjarmasin, 2020)
This study aims to describe the forms of struggle of women leaders in the fields of education, politics, social and economics in the Red Satin novel by Brahmanto Anindito and Rie Yanti. The research data collection was carried out by literary methods and reading and note-taking techniques. Research data were analyzed using the theory of liberal feminism. This research is a descriptive qualitative research with the water model analysis method. The results showed that the form of the struggle of women in the field of education is a struggle in maintaining its existence in the world of work and the struggle to get higher education, in the political field, namely the struggle in obtaining the right to vote and opinion, in the social field, namely the struggle in getting work experience and get a social position, and in the economic field that is struggling in earning income.